PENERAPAN TEKNIK SHOU SUGI BAN PADA DESAIN MEJA KERJA UNTUK MASYARAKAT URBAN : Application Of The Shou Sugi Ban Technique In Work Desk Design For Urban Communities - Rahmawan Dwi Prasetya; Gucci, Revano; Jayadi, Nor (Jurnal Dimensi Seni Rupa dan Desain, 2023)
The new work concept, Flexible Working Space (FWS), is defined as the arrangement of team member work patterns that provide flexibility in work locations by maximizing information technology. This concept encourages the idea of meeting the needs of employees to do activities at home by designing smart and multifunctional work desk products. This workbench is made using reclaimed wood waste and polyester resin. In addition to increasing the selling value, combining wood waste and resin will be realized with the finishing technique of burning (shou sugi ban) on wood. The use of this finishing technique aims to present a classic and elegant aesthetic impression in accordance with user expectations. The design of this work table product uses the Design Thinking method, which consists of 5 stages, namely empathize, define, ideate, prototype, and test. This project produces a smart table, a multifunctional work desk equipped with sensor-based lights and music with reclaimed wood material that is finished using shou sugi tire and resin techniques for the upper-class urban user segment. Keywords: urban, upper class, shou sugi ban, technology